The speciation and genotyping of Cronobacter isolates from hospitalised patients - Alsonosi, A; Hariri, S; Kajsík, M; Oriešková, M; Hanulík, V; Röderová, M; Petrželová, J; Kollárová, H; Drahovská, H; Forsythe, S; Holý, O (European journal of clinical microbiology & infectious diseases, 2015)
The World Health Organization (WHO) has recognised all Cronobacter species as human pathogens. Among premature neonates and immunocompromised infants, these infections can be life-threatening, with clinical presentations of septicaemia, meningitis and necrotising enterocolitis. The neurological sequelae can be permanent and the mortality rate as high as 40-80%. Despite the highlighted issues of neonatal infections, the majority of Cronobacter infections are in the elderly population suffering from serious underlying disease or malignancy and include wound and urinary tract infections, osteomyelitis, bacteraemia and septicaemia. However, no age profiling studies have speciated or genotyped the Cronobacter isolates. A clinical collection of 51 Cronobacter strains from two hospitals were speciated and genotyped using 7-loci multilocus sequence typing (MLST), rpoB gene sequence analysis, O-antigen typing and pulsed-field gel electrophoresis (PFGE). The isolates were predominated by C. sakazakii sequence type 4 (63%, 32/51) and C. malonaticus sequence type 7 (33%, 17/51). These had been isolated from throat and sputum samples of all age groups, as well as recal and faecal swabs. There was no apparent relatedness between the age of the patient and the Cronobacter species isolated. Despite the high clonality of Cronobacter, PFGE profiles differentiated strains across the sequence types into 15 pulsotypes. There was almost complete agreement between O-antigen typing and rpoB gene sequence analysis and MLST profiling. This study shows the value of applying MLST to bacterial population studies with strains from two patient cohorts, combined with PFGE for further discrimination of strains.
Keywords: novorozenec; Infant, Newborn; Infant; feces; vznik druhů (genetika); Humans; Sputum; kojenec; lidé středního věku; dítě; pulzní gelová elektroforéza; Multilocus Sequence Typing; kohortové studie; Child; Female; Aged; mladý dospělý; dospělí; Electrophoresis, Gel, Pulsed-Field; senioři; lidé; Genotype; Cohort Studies; Feces; předškolní dítě; Adult; ženské pohlaví; Inpatients; Male; Middle Aged; sputum; hospitalizovaní pacienti; multilokusová sekvenční typizace; Adolescent; Cronobacter; Aged, 80 and over; Genetic Speciation; Young Adult; Bacterial Typing Techniques; senioři nad 80 let; genotyp; mužské pohlaví; Child, Preschool; techniky typizace bakterií; mladiství